A Short Note on Computing Permutations - Gburzynski, Pawel; Zalewski, Janusz (2023 18th Conference on Computer Science and Intelligence Systems (FedCSIS), 2023)
We discuss an algorithm for generating all permutations of numbers between 1 and N. The algorithm is short and efficient, yet its behavior is not obvious from the code, mostly owing to the recursion. The discussion touches upon a few interesting methodological issues and brings in an educational case study in recursion.